A new ortheziid (Hemiptera: Coccoidea) from Australia associated with Acropyga myops Forel (Hymenoptera: Formicidae) and a key to Australian Ortheziidae - Lapolla, John S.; Burwell, Chris; Brady, Seán G.; Miller, Douglass R. (Zootaxa, 2008)
A peculiar new genus of Ortheziidae is described from Queensland, Australia. Acropygorthezia williamsi LaPolla & Miller, n. gen. & sp. was discovered in two localities in the nests of Acropyga myops. Descriptions and illustrations are provided for the adult female, adult male, first-instar nymph, prepupa, and pupa; descriptions only are provided for the secondand third-instar nymphs. Prior to this study, Acropyga ants were known to enter into trophobiotic relationships only with mealybugs (Hemiptera: Pseudococcidae). Therefore, this study represents the first non-mealybug association between a scale insect and Acropyga. The new ortheziid genus has a number of unusual morphological attributes: no definite wax plates; no ovisac; an anal ring lacking setae and pores, located dorsally in the middle of the abdomen; simple, large metasternal and mesosternal apophyses; numerous spines over the body, and various instars that are so similar that they are difficult to separate. These characteristics may represent adaptations to its relationship with ants. A key is provided to the Australian Ortheziidae.